Incontinentia pigmenti: learning disabilities are a fundamental hallmark of the disease. - Maria Rosa Pizzamiglio; Laura Piccardi; Filippo Bianchini; Loredana Canzano; Liana Palermo; Francesca Fusco; Giovanni D'Antuono; Chiara Gelmini; Livia Garavelli; Matilde Valeria Ursini (PLoS ONE)
Studies suggest that genetic factors are associated with the etiology of learning disabilities. Incontinentia Pigmenti (IP, OMIM#308300), which is caused by mutations of the IKBKG/NEMO gene, is a rare X-linked genomic disorder (1:10000/20:000) that affects the neuroectodermal tissues. It always affects the skin and sometimes the hair, teeth, nails, eyes and central nervous system (CNS). Data from IP patients demonstrate the heterogeneity of the clinical phenotype; about 30% have CNS manifestations. This extreme variability suggests that IP patients might also have learning disabilities. However, no studies in the literature have evaluated the cognitive profile of IP patients. In fact, the learning disability may go unnoticed in general neurological analyses, which focus on major disabling manifestations of the CNS. Here, we investigated the neuropsychological outcomes of a selected group of IP-patients by focusing on learning disabilities. We enrolled 10 women with IP (7 without mental retardation and 3 with mild to severe mental retardation) whose clinical diagnosis had been confirmed by the presence of a recurrent deletion in the IKBKG/NEMO gene. The participants were recruited from the Italian patients' association (I.P.A.SS.I. Onlus). They were submitted to a cognitive assessment that included the Wechsler Adult Intelligence scale and a battery of tests examining reading, arithmetic and writing skills. We found that 7 patients had deficits in calculation/arithmetic reasoning and reading but not writing skills; the remaining 3 had severe to mild intellectual disabilities. Results of this comprehensive evaluation of the molecular and psychoneurological aspects of IP make it possible to place "learning disabilities" among the CNS manifestations of the disease and suggest that the IKBKG/NEMO gene is a genetic determinant of this CNS defect. Our findings indicate the importance of an appropriate psychoneurological evaluation of IP patients, which includes early assessment of learning abilities, to prevent the onset of this deficit.